ANALISIS KAMPANYE POLITIK ANIES BASWEDAN DAN MUHAIMIN ISKANDAR PADA PEMILIHAN UMUM PRESIDEN TAHUN 2024 - Rama Dewa; Hosea Gabriel Memphis Hutapea; Saeful Mujab (Jurnal Komunikasi dan Budaya, 2024)
The political campaigns of Anies Baswedan and Imin Iskandar in the 2024 presidential election are of public interest both nationally and internationally. Anies Baswedan, who is currently the governor of Jakarta, is running as an independent candidate, while Imin Iskandar is a member of the National Awakening Party (PKB) and is running as a vice presidential candidate. The pair are the first to declare that they will compete in the 2024 presidential election. Anies Baswedan has campaigned in various regions, including Jakarta, Southeast Sulawesi, and South Kalimantan, while Imin Iskandar has campaigned in various regions, including Aceh. They have both been active in their efforts to introduce themselves and their political visions to the wider community. During the campaign, Anies Baswedan has been in the media spotlight, including foreign media, highlighting his criticism of the Nusantara project, which is one of the major projects of the current administration. Anies' criticism of this project has attracted the attention of foreign media and become a topic of conversation in the context of the 2024 presidential election. As such, Anies Baswedan and Imin Iskandar's campaign for the 2024 presidential election has attracted public attention, both nationally and internationally, and the pair continues to work on strengthening their support base through various campaign activities and efforts to introduce their political vision to the public.